Deaf education, the active search for students and the proposed bilingual libras-português school in Parnaíba-PI (Research, Society and Development, 2025)
The aim of this study is to analyze the actions and strategies carried out in the active search for deaf students as a way of guaranteeing access and permanence in the bilingual school - libras-português in Parnaíba-PI. Brazilian legislation, considering the Federal Constitution (CF), the Statute of the Child and Adolescent (ECA) and the Law of Guidelines and Bases (LDB), which establish education as a right for all, and the specific laws on inclusive education, do not guarantee its implementation. Students who are deaf or hard of hearing become more marginalized due to the communication barrier, when there is no use of Libras, which is considered indispensable for their development. Consequently, there is a call for urgent measures to ensure that deaf people have bilingual education from an early age. Thus, this qualitative investigation consists of a documentary analysis of the Pedagogical Political Project of the bilingual libras-português school in Parnaíba (PI) and data obtained from open-ended interviews with representatives of the bilingual school, the only one in Piauí, associations and social movements. The results helped to identify challenges and highlight the struggle of philanthropic institutions to maintain and guarantee access, permanence and success, in the face of a scenario of reduced public policies. In this way, we consider the need for educational policies at all levels of government to be designed in tandem with language policies in order to guarantee deaf students' right to quality education.